Canary - Swierczynski, Duane (Mulholland Books, Little, Brown and Company, 2015)
"Honors student Sarie Holland is busted by the local police while doing a favor for her boyfriend. Unwilling to betray him but desperate to avoid destroying her future, Sarie has no choice but to become a "CI" -- a confidential informant. Philly narcotics cop Ben Wildey is hungry for a career-making bust. The detective thinks he's found the key in Sarie: her boyfriend scores from a mid-level dealer with alleged ties to the major drug gangs. Sarie turns out to be the perfect CI: a quick study with a shockingly keen understanding of the criminal mind. But Wildey, desperate for results, pushes too hard and inadvertently sends the nineteen-year-old into a death trap, leaving Sarie hunted by crooked cops and killers alike with nothing to save her -- except what she's learned during her harrowing weeks as an informant. Which is bad news for the police and the underworld. Because when it comes to payback, CI #1373 turns out to be a very quick study..."--Provided from Amazon.com.